Novel technique in the management of large prostate and bladder stones with bipolar transurethral enucleation of the prostate and open cystolithotomy. Issue 4 (November 2016) - Cho, Chak‐Lam; Leung, Clarence LH; Chan, Wayne KW; Chu, Ringo WH; Law, In‐Chak
Abstract : Aim: The surgical management of a large prostate in the presence of large or multiple bladder stones still poses a challenge to urologists. The traditional approach by open prostatic adenomectomy and cystolithotomy carries significant morbidities. However, endoscopic procedure might not be feasible to deal with both conditions in a single procedure, despite advances in surgical techniques and instrumentation. We propose a novel method to manage a large prostate together with significant bladder stone load in a single operation by a combined endoscopic and open approach. Patients and Methods: Three patients had bipolar transurethral enucleation of the prostate (TUEP) and open cystolithotomy performed at our unit from September 2013 to January 2016. The surgical technique and perioperative outcomes are summarized in the present study. Results: The mean age of the patients was 77.3 years. Bipolar TUEP was performed, with a mean pathological specimen weight of 114 g retrieved. All bladder stones were successfully removed by open cystolithotomy. The mean operating time was 158.3 min. Haemoglobin dropped by 2.27 g/dL on average. No transfusion was required. Bladder irrigation was stopped on postoperative day 2. All patients were weaned off the catheter successfully 5–10 days after the operation. Conclusions: Bipolar TUEP and open cystolithotomy is a safe option in managing large prostate and bladder stones in a single procedure.